2013
DOI: 10.1007/s00540-013-1741-2
|View full text |Cite
|
Sign up to set email alerts
|

Taurine attenuates lung ischemia–reperfusion injury after lung transplantation in rats

Abstract: It was demonstrated that donor treatment with taurine resulted in preservation of transplanted lung tissue in respect to histopathological and biochemical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Pretreatment with curcumin significantly prevented the increase in MDA level and the decreased TAS level. In our previous study [1] , we demonstrated that donor treatment with taurine protected the lungs of rats against post-transplantation I/R injury in respect to histopathological and biochemical findings. Following treatment with taurine, we observed increased activities of SOD and CAT, and decreased MDA levels in I/R group compared with taurinetreatment group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment with curcumin significantly prevented the increase in MDA level and the decreased TAS level. In our previous study [1] , we demonstrated that donor treatment with taurine protected the lungs of rats against post-transplantation I/R injury in respect to histopathological and biochemical findings. Following treatment with taurine, we observed increased activities of SOD and CAT, and decreased MDA levels in I/R group compared with taurinetreatment group.…”
Section: Discussionmentioning
confidence: 99%
“…Lung transplantation has become an effective therapeutic option in the treatment of patients with various end-stage pulmonary diseases [1] such as chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis, cystic fibrosis, bronchiectasis, and primary pulmonary hypertension [2] . Lung injury induced by ischemia-reperfusion (I/R) can lead to severe primary graft failure with about 60% mortality after lung transplantation [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effect of taurine has also been attributed to the reduced secretion of interleukins (ILs) (such as IL-8), as shown by experiments in Caco-2 cells, without any participation of polymorphonuclear leukocytes (24). Accordingly, there is a growing body of preclinical data that demonstrates the anti-inflammatory effects of taurine in both neural and systemic inflammation including cardiovascular disease (26), traumatic brain injury (27), liver/gallbladder disease (28), lung injury (29), diabetes (30), cataract (31). As a result, taurine fulfills the necessary criteria to participate in the regulatory network of an immune response.…”
Section: The Role Of Taurine In Inflammationmentioning
confidence: 99%
“…Organ shortage is significant in all transplant medicine, but it is even more acute in LuTx [ 64 ] due to the high incidence of lung injury in potential deceased donors [ 64 ] and the fact that living donor transplantation is extremely complicated [ 65 ]. After transplantation, up to 30% of recipients develop primary graft dysfunction within the first 72 h after reperfusion [ 66 ], which is mainly caused by pulmonary IRI leading to significant postoperative morbidity and mortality [ 67 ].…”
Section: Comprehensive Reviewmentioning
confidence: 99%